INSTRUMENTS, THAT SEARCH AN ENTRANCE POSITION AT INVESTMENT IN A SMALL CAPITALIZATION - A. Gulyatkin (Вестник университета)
The article describes the approaches that analyze financial turnovers and volumes, and that help to identify an optimal range for opening a position, comprised of small capitalization. The author proves low efficiency of classic tools, such as technical analysis, in the context of small capitalization trading. The paper also includes information about life cycles of non-liquid approaches instruments. Basing on theory of volumes and spreads, the author improves the classical analysis, by splitting financial turnovers into call and puts (buying and selling). The author’s new approach for identifying optimal range is based on a combining several certain indicators.